The Current State and Needs of North American Movement Disorders Fellowship Programs - Ludy C. Shih; Daniel Tarsy; Michael S. Okun (Parkinson's Disease)
Background. Movement disorders fellowships are an important source of future clinician-specialists and clinician-scientists for the field. Scant published information exists on the number and characteristics of North American movement disorders fellowship training programs. Methods. A 31-item internet-based survey was formulated and distributed to academic movement disorders listed in the American Academy of Neurology (AAN) directory as having a movement disorders fellowship and to all National Parkinson Foundation Centers of Excellence and Care Centers in North America. Results. There was a 77% response rate among academic movement disorders centers. Broad similarities in clinical training were identified. The two most important rated missions of maintaining a movement disorders fellowship were contributions to scholarly activities and to fulfilling a critical need for specialists. Almost a quarter of fellowship programs did not offer a fellowship slot during the most recent academic year. Fellowship directors cited a wide variety of funding sources, but their top concern was lack of available funding for fellowship programs. Conclusions. North American movement disorders fellowship training programs currently offer similar methods of clinical training and education. Lack of funding was the most important obstacle to maintaining fellowship programs and should be made a priority for discussion in the field.